Drought Stress Triggers Shifts in the Root Microbial Community and Alters Functional Categories in the Microbial Gene Pool - Xie, Jianbo; Dawwam, Ghada E.; Sehim, Amira E.; Li, Xian; Wu, Jiadong; Chen, Sisi; Zhang, Deqiang (Frontiers in Microbiology, 2021)
Drought is a major threat to crop productivity and causes decreased plant growth, poor yields, and crop failure. Nevertheless, the frequency of droughts is expected to increase in the coming decades. The microbial communities associated with crop plants can influence how plants respond to various stresses; hence, microbiome manipulation is fast becoming an effective strategy for improving the stress tolerance of plants. The effect of drought stress on the root microbiome of perennial woody plants is currently poorly understood. Using Populus trees as a model ecosystem, we found that the diversity of the root microbial community decreased during drought treatment, and that compositional shifts in microbes during drought stress were driven by the relative abundances of a large number of dominant phyla, including Actinobacteria, Firmicutes, and Proteobacteria.A subset of microbes including Streptomyces rochei, Bacillus arbutinivorans, B. endophyticus B. megaterium, Aspergillus terreus, Penicillium raperi, Trichoderma ghanense, Gongronella butleri, Rhizopus stolonifer were isolated from the drought-treated poplar rhizosphere soils, which have potentially beneficial to plant fitness. Further controlled inoculation experiments showed that the isolated bacterial and fungal isolates positively impacted plant growth and drought tolerance. Collectively, our results demonstrate the impact of drought on root microbiome structure and provide a novel example of manipulating root microbiomes to improve plant tolerance.